The Influence of Level of Education, Training and Work Discipline on the Performance of Forestry Officials in Makassar - Herman Jelatu; Lucas Maria; Jayshree Martin (Journal Markcount Finance, 2023)
This study aims to determine the effect partially and simultaneously the level of education, training, and work discipline partially affect the performance of employees in the Makassar Forestry Service. To determine the level of education, training, work discipline on the performance of employees in the Makassar Forestry Service. This study uses a quantitative approach. Data analysis techniques in this study used validity tests, reliability tests, multiple linear regression analysis, partial tests, and simultaneous tests. From the results of the validity test, the data shows valid with the R-count greater than the R-table. Based on the multiple linear regression analysis the results of the analysis are: Y = 42.460 + 0.050X1 + 0.830X2 + 0.857X3. It is known that the level of education, training and work discipline has a partial effect on the performance of forestry service employees in Makassar. Where each variable t-count value is greater than t-table, education level (2.362 > 1.699), training (1.974 > 1.699), work discipline (2.232 > 1.699) and simultaneous test scores show f-count greater than f -table (2.986 > 2.96). This means that the level of education, training, and work discipline simultaneously affect the performance of forestry service employees in Makassar.